The 'rehabilitation sciences' research funding programme: research findings -- implementation -- impact and perspectives. - Zwingmann C; Buschmann-Steinhage R; Gerwinn H; Klosterhuis H (Rehabilitation, 2004)
In 1998, the German Federal Ministry of Education and Research (BMBF) and the German pension insurance scheme established a funding programme for research in rehabilitation. This 'Rehabilitation Sciences' research funding programme comprises eight regional research networks for eight years in two periods (1998-2002, 2001-2005). In our paper we review the findings of the first funding period in five of the research fields: patient education, need for and access to rehabilitation, vocational training in medical rehabilitation to enhance return to work, comorbid mental disorders in patients with somatic diseases, and gender differences. Several activities aimed at transferring research findings into practice are outlined. Finally, the impact of the funding programme is summarized and perspectives for further funding are given.